Kompetensi Aparatur Bagian Umum Dan Kepegawaian Bkpsdm Kota Mataram Dalam Menjalankan Tupoksinya Sesuai Perwali Nomor 61 Tahun 2016 - Umami, Rizal; Hidayatullah, Hidayatullah; Rachman, M. Taufik (JIAP (Jurnal Ilmu Administrasi Publik), 2022)
the purpose of this study is to analyze the competence of the apparatus of the general staffing section of the BKPSDM Personnel Board of the City of Mataram in carrying out its duties based on the Mayor's Regulation Number 61 of 2016, based on this regulation, the duties and functions of the BKPSDM in general, namely related to general service administration of personnel and preparation of policy planning for Mayor regulations Mataram. The type of research used is a qualitative descriptive approach, data collection techniques using interviews, observation and documentation. The results of the study show that the performance of the apparatus of the general division and staffing of the Mataram City BKPSDM is competent in carrying out its duties and functions as the implementation of regional government affairs in the field of personnel administration and the development of apparatus resources, especially those of echelon II, III and IV, but the thing that needs to be addressed is the apparatus apparatus below that is directly related to public services, so it is necessary to carry out comprehensive education and training (training) in order to achieve competent and responsible apparatus.